Treatment-Emergent Adverse Events in Gene Therapy Trials for Inherited Retinal Diseases: A Narrative Review - Nuzbrokh, Yan (Ophthalmol Ther, 2020)
Patient safety is a primary priority in the conduction of retinal gene therapy trials. An understanding of risk factors and mitigation strategies for post-procedure complications is crucial for the optimization of gene therapy clinical trial protocols. In this review, we synthesize the literature on ocular delivery methods, vector platforms, and treatment-emergent adverse effects in recent gene therapy clinical trials for inherited retinal diseases.